131I-Chlorotoxin dosimetry in liver using MCNP simulation code - Amiri, Jamal; Shirmardi, Seyed Pezhman; Adeli, Rohollah; Erfani, Mostafa; Saniei, Elham; Vafaee, Reza; Imanzad, Masoumeh (Archives of Advances in Biosciences, 2013)
Chlorotoxin is a 36 amino acids peptide, which is able to block chloride channels isolated from mouse brain. A derivative of chlorotoxin is synthesized and it is labeled by iodine 131; then animal experiments carry out on rats. Multiple organ doses may be calculated with biological distribution results in rats with labeled compounds using simulated MCNP4C code. Human dose can be calculated using the dose distribution in rats with a conversion ratio for dose distribution. Chloramine T is our method for marking, and electrophilic substitution reactions are methods for iodize of peptides. Simulation of a human phantom to evaluate dose distribution was done using simulation code MCNP4C. To evaluate the dose distribution in the human body, using this code and the accumulated activity in each organ tissue dose is calculated. To study the biological distribution of the radiotracer 131I, 0.37 MBq radiotracer was injected into rat via the tail vein. The accumulated activity in each organ with the agent “ID / g” is determined. Biological distribution of 131I-chlorotoxine in the normal rats is obtained. Its Decay constant in the liver is 0.07h and the effective half-life of the radiotracer is 10h in rat liver. The total number of particles found in the leak from liver tissue was reported 67600. Liver tissue dosimetries originating from other sources (thyroid tissue, stomach, kidney, right & left lung, spleen, and pancreas) were examined. Then, the overall dose to the target tissue will be calculated. Leaked beta particles in liver itself (self-dose) are the most delivered dose to the liver (98%); it is for gamma rays 1.1%, while its source is adjacent tissues in addition to liver (cross-dose); Because of low atomic number of the tissue, delivered dose originated from Bremsstrahlung (braking radiation) is low (0.9%). Radiation dose to the liver in intravenous injection of 0.37 MBq 131I-chlorotoxine radiotracer is 3.44 * 10-6.